Community Empowerment Strategy Based on Local Wisdom in the Development of Cikakak Tourism Village - Sari, Novita; Suksmadi, Ignatius; Mutahir, Arizal (Devotion : Journal of Research and Community Service, 2025)
Cikakak Village was designated as an advanced category tourist village based on the Banyumas Regent Decree Number /556/166/Year 2020, established on March 20, 2020. Based on literature review, many studies have not yet addressed the aspect of empowerment strategies based on local wisdom in developing a tourist village into an advanced tourist village. Therefore, this study aims to examine the community empowerment strategies based on local wisdom in developing Cikakak Village into an advanced tourist village. This is important so that the success of this village can serve as an example or model for other tourist villages to improve their classification to become advanced tourist villages. This research was conducted using a qualitative method. The subjects of this study were the managers of Cikakak Tourist Village and parties familiar with the management activities of Cikakak Tourist Village. Informants were selected using purposive sampling. Data collection methods included observation, in-depth interviews, and documentation. Data analysis was conducted using interactive analysis according to Miles and Huberman. The results of this study indicate that the development of Cikakak Tourist Village is carried out through a series of strategies focused on community empowerment based on local wisdom. The empowerment approach based on local wisdom aims to maximize the utilization of natural wealth, cultural heritage, as well as local skills and knowledge passed down through generations. The strategies implemented include preserving religious and cultural activities as the identity of Cikakak Tourist Village, innovating craft and culinary products unique to Cikakak Tourist Village, and promoting Cikakak Tourist Village through social media, collaboration, and participation in tourist village competitions.